HERMENEUTIKA, MAKNA, DAN KOMUNIKASI DALAM PERSPEKTIF HANS-GEORG GADAMER - Constantin, Natasha; Sitorus, Fitzerald (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2024)
This research examines the concept of understanding and meaning in communication from the viewpoint of Hans-Georg Gadamer. It focuses on hermeneutics, which is the skill of accurately comprehending the message transmitted by another person via language. According to Gadamer, hermeneutics is seen as a method of interpretative comprehension that is used to bring out an interpretation of the communicated message. This research emphasizes the significance of comprehending in hermeneutics for the interpretation of the current state of affairs. This research further investigates the impact of Gadamer's perspective on the concept of meaning and comprehension within the realm of communication.